Effect of NaCl Concentration in Quenching Medium on Microstructure, Hardness, and Corrosion Behavior of AISI 4140 Steel - Syaripuddin; Sopiyan; Rany Anggraini; Adi Tri Tyassmadi; Silalahi Jose Jan Filder; Muhammad Dhafa Irziansyah; Syamsuir; Ahmad Lubi; Muhammad Fatihuddin; Reza Febriano Armas; Ferry Budhi Susetyo (Jurnal ASIIMETRIK Jurnal Ilmiah Rekayasa & Inovasi, 2026)
AISI 4140 steel is widely used in engineering and marine components due to its high strength and good hardenability. However, improving hardness through heat treatment may influence the corrosion behavior of the material in chloride containing environments. This study investigates the effect of NaCl concentration as a quenching medium on the microstructure, hardness, and corrosion behavior of AISI 4140 steel. The samples were austenitized at 1000 °C for 15 minutes and quenched in NaCl solutions with concentrations of 3.5%, 7%, and 10.5%. Microstructural observations were carried out using optical microscopy after etching with 3% Nital. Hardness testing was performed using the Vickers method with a 10 kg load, while corrosion behavior was evaluated using weight loss measurements and electrochemical tests in 3.5% NaCl solution. The results show that increasing NaCl concentration produces a finer martensitic structure and increases hardness from 673 VHN at 3.5% NaCl to 762 VHN at 10.5% NaCl. However, the corrosion rate also increases from 0.3688 mmpy to 0.3990 mmpy, indicating higher electrochemical activity at the material surface. These results demonstrate a trade-off between improved hardness and reduced corrosion resistance with increasing NaCl concentration.